Optimizing production planning efficiency and sustainability using multi-objective decision making and goal programming - Eileen Haas Jung; Aschari Reinhard Laamanen (International Enterprise Integration Association, 2022)
Optimization of production planning efficiency and sustainability is crucial for organizations aiming to achieve operational excellence while minimizing their environmental footprint. This research proposes a novel approach that combines Goal Programming and Multiple Criteria Decision Making (MCDM) techniques to address the multi-objective nature of production planning. The study develops a mathematical formulation that considers objectives such as production efficiency, cost minimization, environmental impact reduction, and adherence to sustainability targets. A decision support system is designed to assist decision-makers in evaluating trade-offs and identifying the most suitable compromise solution. The research employs a numerical example to demonstrate the effectiveness of the proposed approach, showcasing how production quantities and sustainability practices can be optimized. The results highlight the ability of the approach to strike a balance between efficiency and sustainability, providing decision-makers with a comprehensive framework to make informed decisions aligned with sustainability goals. This research contributes to the existing literature by offering a practical methodology that enhances production planning processes, leading to more sustainable and efficient operations